2023
DOI: 10.1007/s12565-023-00717-7
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor and perineal muscles: a dynamic coordination between skeletal and smooth muscles on pelvic floor stabilization

Abstract: The purpose of this review is to present our researches on the pelvic outlet muscles, including the pelvic floor and perineal muscles, which are responsible for urinary function, defecation, sexual function, and core stability, and to discuss the insights into the mechanism of pelvic floor stabilization based on the findings. Our studies are conducted using a combination of macroscopic examination, immunohistological analysis, 3D reconstruction, and imaging. Unlike most previous reports, this article describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 108 publications
(270 reference statements)
0
3
0
Order By: Relevance
“…A part of the LA is known to attach to the lateral aspect of the vagina, and this structure is believed to influence the proximal position of the urethra (DeLancey & Starr, 1990 ). This connection between the LA and the vagina is not a result of LA muscle fibres inserting into the vaginal wall, but rather smooth muscle fibres extending from the vaginal wall interlocking with the medial surface of the LA skeletal muscle bundles to form a solid interface: skeletal muscle sandwiched by smooth muscle and smooth muscle inserting into skeletal muscle (DeLancey & Starr, 1990 ; Kato et al., 2020 ; Muro & Akita, 2023b ). Therefore, the LA‐a may also contribute to the support and elevation of the vagina and stabilisation of the proximal urethral position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A part of the LA is known to attach to the lateral aspect of the vagina, and this structure is believed to influence the proximal position of the urethra (DeLancey & Starr, 1990 ). This connection between the LA and the vagina is not a result of LA muscle fibres inserting into the vaginal wall, but rather smooth muscle fibres extending from the vaginal wall interlocking with the medial surface of the LA skeletal muscle bundles to form a solid interface: skeletal muscle sandwiched by smooth muscle and smooth muscle inserting into skeletal muscle (DeLancey & Starr, 1990 ; Kato et al., 2020 ; Muro & Akita, 2023b ). Therefore, the LA‐a may also contribute to the support and elevation of the vagina and stabilisation of the proximal urethral position.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, pelvic organ prolapse is strongly associated with injury to the levator ani (LA) (DeLancey et al., 2003 ; Lien et al., 2004 ; Miller et al., 2010 , 2015 ). The LA is the largest muscle that provides support to the pelvic organs and, in tandem with the coccygeus, constitutes the pelvic diaphragm (pelvic floor muscle) (Muro & Akita, 2023b ). LA function is indispensable for pelvic floor support and is closely related to pathologies such as urinary incontinence and pelvic organ prolapse in women; therefore, its anatomy has received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that pelvic floor muscles, including perineal muscles and the external anal sphincter, share muscle bundles and are continuous [7–10]. Thus, we speculated that the external urethral sphincter may also be continuous with surrounding skeletal muscles.…”
Section: Introductionmentioning
confidence: 96%